Biosynthesis and metabolism of plant glycosides : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University - Tapper, Brian Anthony (Massey University, 1968)
The biosynthesis of selected cyanogenic glucosides and glucosinolates was examined in higher plants. Linen flax seedling shoots (linum usitatissimum L.) were used exclusively to study linamarin biosynthesis while prunasin biosynthesis was studies in both peach shoots (Prunus persica Batsch) and cherry laurel shoots (P. laurocerasus L.). Isoprppylglucosinolate and benzylglucosinolate were studied in scurvy grass seedlings (Cochlearia officinalis L.) and garden cress seedling shoots (Lepidum sativum L.) respectively. Altogether 9 isotopically labelled compounds were prepared as part of the study and 14 were administered to plant tissue. The quantity of cyanogenic glucosides was determined by measuring hydrogen cyanide following enzymic hydrolysis. The specific activity or dilution of the labelled compound after incorporation into the glucosides was determined and sued to judge the effectiveness of the administered compound as a precursor of the glucosides. Benzaldehyde from prunasin was measured as its semicarbazone and the isothicyanates. Obtained by enzyme hydrolysis of the glucosinolates, were identified by conversion to thiourea derivatives. Paper and thin layer chromatography and electrophoresis were used to separate non-volatile radioactive compounds. Isobutyraldoxime-U-14C, 2-oximinoisovaleric acid-U-14C, isobutyronitrile-1-14C and 2-hydroxyisobutyronitrile-1-14C were all incorporated into linamarin to extents comparable to that from L-valine-U-14c. By the use of 15N labelled compounds the C-N bond of isobutyraldoxime and 2-oximinoisovaleric acid was shown to remain intact during the cornversjon to linarnarin. Isobutyramide-1-14C and hydrogen cyanide-14c were not significantly incorporated into linamarin. Phenylacetaldoxime-U-14C, 2-oximino-3-phenylpropionic acid-2-14C and phenylacetonitrile-1-14c were converted to prunasin to greater extents than was L-phenylalanine-U-14C. Radioactivity from D,L-mandelonitrile-1-14C and, to a lesser extent, from hydrogen cyanide-14-C was also incorporated into the nitrile moiety of prunasin. Phenylacethydroxamic acid-1-14C was not significantly converted to prunasin. Linen 'lax seedling shoots were examined for both volatile and non-volatile intermediates. Radioactive precursors of linamarin were administered in the presence of other suspected intermediates or inhibitors of linamarin biosynthesis. Both isobutyraldoxime and isobutyronitrile were shown to be formed in the shoots from L-valine-U-14C. A non-volatile compound which accumulated in the presence of a few inhibitors Of linamaran biosynthesis was studied in detail. Treatment with acid under mild conditions yielded isobutyraldehyde while emulsin gave isobutyraldoxime. It was resistant to linamarase. Isobutyronitrile was a product of pyrolysis. The proposed structure for this compound is isobutyraldoxime-0-glucoside. Isobutyraldoxime-U-14C and phenylacetaldoxime-U-14C were both better precursors of the corresponding glucosinolates than were L-valine-U-14C or L-phenylalanine-U-14C. 2-Oximinoisovaleric acid-U-14C was not significantly incorporated into isopropylglucosinolate. It is concluded that aldoximes are intermediates in the biosynthesis of both cyanogenic glycosides and glucosinolates. Other intermediates proposed in cyanogenic glycoside biosynthesis are nitriles and 2-hydroxynitriles in that order, N-Hydroxyamino acids may be intermediates between amino acids and aldoximes. 2-Oximino acids may also be intermediates in cyanoglycoside biosynthesis although it is possible that the observed incorporation was by way of prior non-enzymic conversion to nitriles. The experiments with labelled administered compounds have outlined a pathway of cyanogenic glycoside biosynthesis which may now be profitably studied for confirmation at the enzymic level.
Content removed due to copyright restrictions: Tapper, B., Conn, E., & Butler, G. (1967). Conversion of alpha-keto-isovaleric acid oxime and isobutyraldoxime to linamarin in flax seedlings. Archives Of Biochemistry And Biophysics, 119(1), 593-595. Tapper, B. A., & Butler, G. W. (1967). Conversion of oximes to mustard oil glucosides (glucosinolates). Arch. Biochem. Biophys, 120, 719-721 Hahlbrock, K., Tapper, B., Butler, G., & Conn, E. (1968). Conversion of nitriles and alpha-hydroxynitriles to cyanogenic glucosides in flax seedlings and cherry laurel leaves. Archives Of Biochemistry And Biophysics, 125(3), 1013-1016. Bennet, W.D.& Tapper, B. (1968). A sensitive method for detecting cyanoglycosides on paper and cellulose thin layers. Journal Of Chromatography A, 34, 428-429
Keywords: Glycosides; Plant glycosides; Metabolism; Biosynthesis; Biochemistry